2014
DOI: 10.1055/s-0033-1356383
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Conventional Rib Series in Patients with Minor Thoracic Trauma

Abstract: Hintergrund: Hemithoraxaufnahmen (HT) sind eine spezielle radiografische Technik zur Darstellung der knöchernen Anteile der Thoraxwand. Die Technik findet häufig Anwendung in der Evaluation von Bagatelltraumen des Thorax, oft in Kombination mit Thoraxübersichtsaufnah-men (THÜ Background: Conventional rib series (RS) represent a dedicated radiographic technique to visualize the bony parts of the chest wall. The method is commonly used to evaluate minor thoracic trauma, frequently in combination with chest radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…Moreover, these authors found that, compared to standard PA radiographs, rib series negatively impacted patient care by prolonging report turnaround time [10]. Hoffstetter et al [11] retrospectively reviewed 609 patients that underwent rib series in the emergency department and found that while diagnosing a higher number of rib fractures as compared to PA radiographs alone, there was no statistically significant difference in the number of patients who received medical treatment. If rib series are to be performed, Park et al [12] showed that interpreting images with both conventional grayscale and inverted grayscale views may improve detection of rib fractures, although this study did not assess if the improved detection had an effect on outcomes.…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Ribmentioning
confidence: 99%
“…Moreover, these authors found that, compared to standard PA radiographs, rib series negatively impacted patient care by prolonging report turnaround time [10]. Hoffstetter et al [11] retrospectively reviewed 609 patients that underwent rib series in the emergency department and found that while diagnosing a higher number of rib fractures as compared to PA radiographs alone, there was no statistically significant difference in the number of patients who received medical treatment. If rib series are to be performed, Park et al [12] showed that interpreting images with both conventional grayscale and inverted grayscale views may improve detection of rib fractures, although this study did not assess if the improved detection had an effect on outcomes.…”
Section: Discussion Of Procedures By Variant Variant 1: Suspected Ribmentioning
confidence: 99%
“…Konservatif tedavi kararı alınan nondeplase kosta fraktürü olan hastalarda daha sonra gelişebilecek atelektazi ve pnömoninin önlenebilmesi için iyi ağrı yönetimi ve dolayısıyla iyi akciğer ventilasyonu sağ-lanmalıdır. Deplase kosta fraktürü için konservatif ya da cerrahi kararı ise hâlâ tartışmalıdır (2,9) . Travma sonrası akciğer herniasyonu tedavisinde ise genellikle cerrahi tedavi önerilmektedir.…”
Section: Discussionunclassified
“…Toraks travmalarının %70'i motorlu araç kazaları sonrası, %10-17'si yüksekten düşme sonrası meydana gelmektedir (2) . Künt toraks travmalarında en sık (hastaların yaklaşık %50'sinde) yaralanan iskelet sistemi komponenti kostalar olmaktadır (3) .…”
Section: Introductionunclassified
“…Radiography focused on the ribs has been reported to be useful for the diagnosis of rib fractures. [3][4][5] It is easily performed, except in patients with severe pain. Cough-induced rib fractures often occur in the middle and lower ribs.…”
Section: Discussionmentioning
confidence: 99%